التنمر المدرسي لدى تلاميذ مرحلة التعليم الثانوي "دراسة على عينة من تلاميذ مرحلة التعليم الثانوي بمدينة غرداية" - علاوي, اسية; الشايب, خولة (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة إلى معرفة مستوى التنمر لدى تلاميذ المرحلة الثانوية، والتعرف على الفروق في مستوى التّنمر المدرسي لدى تلاميذ المرحلة الثانوية حسب الجنس والمستوى الدراسي. ولتحقيق أهداف الدراسة تم استخدام المنهج الوصفي، ولجمع البيانات تم الاعتماد على مقياس التنمر المدرسي الذي أعدّه الصبحيين والقضاة (2013) بعد التأكد من صلاحيته لمجتمع الدراسة، حيث طُبق على عينة مكونة من (200) تلميذ وتلميذة من تلاميذ المرحلة الثانوية بثانوية "عبد الحميد بن باديس" وثانوية "بوهراوة" بمدينة غرداية. وبعد تحليل البيانات إحصائياً أظهرت النتائج أن (98%) من تلاميذ المرحلة الثانوية يمارسون التنمر بدرجة منخفضة، وأن التلاميذ منخفضي التحصيل الدراسي أكثر تنمراً من التلاميذ مرتفعي التحصيل الدراسي، كما أظهرت وجود فروق دالة إحصائياً في سلوك التّنمر المدرسي لدى تلاميذ المرحلة الثانوية حسب الجنس لصالح الذكور، وعدم وجود فروق دالة إحصائياً في سلوك التّنمر المدرسي لدى تلاميذ المرحلة الثانوية تعزى للمستوى الدراسي. Abstract: The study aimed to know the level of bullying among secondary school students, and to identify the differences in the level of school bullying among secondary school students by gender and academic level. The descriptive approach was used, and reliance on the school bullying scale prepared by Al-Subhiyin and Al-Qudah (2013), which was applied to a sample of (200) male and female students from the secondary school students "Abdel Hamid Ben Badis" and "Bohraoua" in Ghardaia. The results showed that (98%) of secondary school students practice bullying to a low degree, and that students with low academic achievement are more bullying than students with high academic achievement, and there are statistically significant differences in school bullying behavior among secondary school students by gender in favor of males, and there are no significant differences Statistically in the behavior of school bullying among secondary school students due to the academic level.
School bullying among secondary school students A study on a sample of secondary school students in the city of Ghardaia
مقال
Keywords: تنمر مدرسي، تحصيل دراسي، تلاميذ المرحلة الثانوية، مستوى الدراسي.; school bullying; Academic achievement; secondary school students; academic level.